Cancel (Out) Emissions? The Envisaged Role of Carbon Dioxide Removal Technologies in Long-Term National Climate Strategies - Buylova, Alexandra; Fridahl, Mathias; Nasiritousi, Naghmeh; Reischl, Gunilla (Frontiers in Climate, 2021)
Carbon dioxide removal (CDR) increasingly features in climate scenarios that hold global warming well below 2 °C by 2100. Given the continuous gap between climate mitigation pledges and the emission pathways that are aligned with achieving the temperature goals of the Paris Agreement, we would expect countries to promote CDR in their long-term planning to achieve mid-century targets. Yet, it is also not obvious that countries consider it their fair share to contribute to the mitigation efforts with CDR technologies and approaches. Therefore, studying countries’ long-term climate plans is timely and vital. Such studies can reveal the pledged collective ambition, the contribution of CDR in it, and how the envisaged role of CDR is described by different countries. This paper explores countries’ long-term low emission development strategies (LT-LEDS) in order to map the role of CDR in addressing climate change. We also supplement our examination of strategies with opinions of climate experts. Based on an inductive coding of the material and a literature review, the analytical focus of the analysis includes CDR targets and planning, CDR types, barriers and opportunities to CDR implementation, and international cooperation. Our study of 25 national LT-LEDS submitted to the UN or to the EU, as well as 23 interviews with climate experts, shows that national plans on CDR vary substantially across countries and generally lack in detail. The findings also demonstrate that CDR is perceived to be necessary and desired for achieving mid-century climate goals, but also reveal variation in what the role of CDR should be. We use an interpretive approach to outline three possible visions of CDR in climate action: as a panacea, as a necessary fallback, and as a chimera. These highlight different understandings of the envisaged role of CDR in addressing climate change. This research thereby contributes to the literature on governing CDR with new comprehensive insights into countries’ long-term climate strategies.